Powder coating for reflective mark as well as preparation method and application of powder coating

By optimizing the formulation and process of powder coatings, using materials such as epoxy resin, end-carboxylic polyester resin and modified glass beads, the problem of incompatibility between glass beads and substrates in the prior art is solved, and the reflective performance and service life are significantly improved.

CN119799122APending Publication Date: 2025-04-11SHANDONG QIANJIANG POWDER TECH CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411979187.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-31
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

In the prior art, when preparing powder coatings for reflective markings, glass microbeads are incompatible with the matrix formula components and are not easily dispersed, the interface bonding effect is poor and the crushing rate is high, resulting in poor coating effect, reflective material is easy to peel off, and reflective effect is poor.

Method used

Components A and B composed of epoxy resin, end carboxylic polyester resin, modified glass beads, etc. are used to optimize the formulation and process to form a base coat and a top coat to improve the dispersion stability and interface compatibility of the glass beads.

Benefits of technology

It significantly improves the reflective performance of powder coatings, extends the service life of reflective materials, and ensures the long-term stability and high gloss of the coating.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005221128050000131
    Figure BDA0005221128050000131
  • Figure BDA0005221128050000141
    Figure BDA0005221128050000141
  • Figure BDA0005221128050000151
    Figure BDA0005221128050000151
Patent Text Reader

Abstract

The invention discloses a powder coating for a reflective mark as well as a preparation method and application of the powder coating, and belongs to the technical field of powder coating preparation. Epoxy resin and carboxyl-terminated polyester resin are preferably selected in the component A of the priming coat and interact with other components, the priming coat can have more excellent adhesive force and corrosion resistance with a base material, and silver-plated mirror surface aluminum powder which is not prone to oxidation is added, so that the priming coat can be endowed with more excellent light reflectivity, and the high gloss of the priming coat in long-term use can be guaranteed. The preferable main component in the component B of the surface coating is carboxyl-terminated polyester resin, and the component B interacts with other components and is good in interfacial compatibility with the bottom coating, and the component B has high permeability and can endow the powder coating with remarkable reflective performance under the synergistic interaction effect of the modified glass beads. On the whole, after the formula and the process are optimized, the powder coating with a remarkable light reflecting effect can be obtained, and the powder coating is suitable for the fields of traffic safety, building decoration, consumption emergency and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of powder coating preparation, and in particular to a powder coating for reflective marking and a preparation method and application thereof. Background Art

[0002] In order to ensure traffic safety and reduce accidents, road signs are indispensable. Most of the road sign paints currently used in China do not have reflective properties, and the signs are poor at night. The main measure to improve the traffic signs of various roads is to study and use reflective materials with excellent reflective properties. Reflective materials are based on the principle of retroreflection. They can use the irradiation of car lights and the reflection of light to increase the distance at which drivers can find objects in front, thereby giving drivers more time to take corresponding safety measures. Reflective powder is generally required to be added to reflective materials. Reflective powder in the prior art is generally produced from glass bead powder materials, namely: ND≥1.90, ND≥1.93, ND≥2.2, and the specifications can be graded from 100 mesh to 800 mesh, and the colors are gray and white. The reflective principle of glass beads is that when light is irradiated on the surface of glass beads, due to the high refraction of glass beads, it focuses on the special reflective layer at the focus of glass beads. The reflective layer reflects the light through transparent glass beads and reflects it back to the vicinity of the light source, so very bright reflected light can be seen at the light source. According to complex optical formulas, a good retro-reflective effect can only be achieved when the refractive index of the glass beads is greater than 1.9.

[0003] There are also schemes in the prior art that use glass beads as reflective materials in coatings. For example, the Chinese patent application number CN202310094402.1 discloses a pearlescent glittering anti-fouling coating, and the coating product has the characteristics of high glitter, high gloss, high chroma and good weather resistance. For example, the Chinese patent application number CN202210591178.2 discloses a high antistatic powder coating and its preparation method, which uses barium titanate and hollow glass beads as composite conductive fillers to improve the antistatic properties of the material. Although the coating also has a certain glittering effect, the glass beads are easy to peel off and the reflective effect is not good. In addition, in the process of preparing powder coatings for reflective signs in the prior art, there are also problems such as incompatibility between glass beads and matrix formula components, difficulty in dispersion, poor interface bonding effect and high breakage rate, which leads to poor coating effect, easy peeling of reflective materials and poor reflective effect. Summary of the invention

[0004] Based on this, in order to solve the problems that the glass beads are incompatible with the matrix formula components, are not easy to disperse, have poor interface bonding effect and high breakage rate in the process of preparing powder coatings for reflective markings in the prior art, which leads to poor coating effect, easy peeling of reflective materials and poor reflective effect, the present invention provides a powder coating for reflective markings and a preparation method and application thereof, and the specific technical scheme is as follows:

[0005] A powder coating for reflective marking, the powder coating comprising component A capable of forming a base coating and component B capable of forming a top coating;

[0006] Wherein, the component A comprises the following raw materials in parts by weight:

[0007] 30 to 45 parts of epoxy resin, 30 to 45 parts of carboxyl-terminated polyester resin, 5 to 35 parts of transparent powder, 0.5 to 2 parts of leveling agent, 0.5 to 2 parts of brightener, 0.5 to 1 part of adhesion promoter, 0.2 to 0.5 parts of benzoin, 0.5 to 2 parts of defoamer, 0.5 to 2 parts of antioxidant, 0 to 1 part of pigment, 0.5 to 1 part of aligning agent, 0.5 to 1.5 parts of silver-plated mirror aluminum powder and 0.1 to 0.2 parts of desiccant;

[0008] Wherein, the component B comprises the following raw materials in parts by weight:

[0009] 80 to 95 parts of terminal carboxyl polyester resin, 6 to 7 parts of triglycidyl isocyanurate, 2 to 10 parts of modified glass microspheres, 0.5 to 2 parts of leveling agent, 0.2 to 0.5 parts of anti-scratch agent, 0.2 to 0.5 parts of benzoin, 0.5 to 1 parts of antioxidant, 0.2 to 0.5 parts of ultraviolet absorber and 0.1 to 0.2 parts of desiccant.

[0010] Furthermore, in component A, the epoxy value of the epoxy resin is 0.098 eq / 100 g to 0.143 eq / 100 g, and the softening point is 89° C. to 99° C.

[0011] Furthermore, in component A, the acid value of the carboxyl polyester resin is 60 mgKOH / g to 75 mgKOH / g, and the softening point is 95 to 120°C.

[0012] Furthermore, in component B, the acid value of the carboxyl-terminated polyester resin is 32 mgKOH / g to 38 mgKOH / g, the viscosity @200°C (mPa.s) is 1500 to 2500, and the glass transition temperature is 64 to 67°C.

[0013] Furthermore, the preparation method of the modified glass microspheres is:

[0014] Mixing vinyl trimethoxy silane and vinyl triethoxy silane in a mass ratio of (1 to 5): (1 to 3) to obtain a treating agent;

[0015] Glass microbeads of different particle sizes are added to a mixture containing stearyltrimethylammonium chloride, ethyl acetate and water, stirred at a speed of 100 r / min to 150 r / min for 20 min to 30 min, then sprayed with the treating agent in a rotary dryer at a speed of 10 r / min to 20 r / min and a temperature of 80°C to 90°C, and the rotary treatment is continued for 2h to 3h under the same rotary conditions to obtain modified glass microbeads.

[0016] Furthermore, the glass microspheres are mixed by the following particle size ratios in mass percentage: 10 μm to 30 μm particle size accounts for 15% to 20%, 31 μm to 50 μm particle size accounts for 25% to 30%, 51 μm to 80 μm particle size accounts for 30% to 35%, 81 μm to 120 μm particle size accounts for 7% to 10%, and 121 μm to 150 μm particle size accounts for 5% to 10%.

[0017] In addition, the present invention also provides a method for preparing a powder coating, which is used to prepare the powder coating for the reflective marking, and the method comprises the following steps:

[0018] Add epoxy resin, carboxyl-terminated polyester resin, transparent powder, leveling agent, brightener, adhesion promoter, benzoin, defoamer, antioxidant, pigment and aligning agent into a mixing device and mix them evenly, and then perform a first melt extrusion and a first ACM grinding process to obtain a mixture;

[0019] Adding the silver-plated mirror aluminum powder, the desiccant and the mixture into a bonding device for bonding treatment, and then sieving to obtain component A capable of forming a primer layer;

[0020] Add the terminal carboxyl polyester resin, triglycidyl isocyanurate, modified glass microbeads, leveling agent, anti-scratch agent, benzoin, antioxidant, ultraviolet absorber and desiccant into a mixing device and mix evenly, and then undergo a second melt extrusion and a second ACM grinding process to obtain component B that can form a topcoat.

[0021] Furthermore, the conditions for the first melt extrusion are: a screw speed of 40 Hz to 45 Hz, a melting zone temperature of 90° C. to 105° C., and a mixing zone temperature of 110° C. to 120° C.

[0022] Furthermore, the bonding treatment conditions are as follows: bonding temperature is 25°C to 35°C, cold bonding speed is 900rpm to 1000rpm, cooling speed is 400rpm to 500rpm, cold water temperature is 17°C to 19°C, and bonding stage time is 600s to 900s.

[0023] In addition, the present invention further provides an application of the powder coating, wherein the application is the application of the powder coating in a road reflective sign, and the application method is:

[0024] The substrate is pretreated, and then component A is sprayed on it, placed in a curing furnace, and cured at a temperature of 150°C for 10 minutes to form a primer layer with a thickness of 60μm to 100μm; after being taken out of the furnace, component B is sprayed on it, and then placed in a curing furnace, and cured at a temperature of 210°C for 15 minutes to form a top coating layer with a thickness of 100μm to 150μm.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. Component A of the primer layer of the present invention preferably contains epoxy resin and carboxyl-terminated polyester resin, which interact with other components to have better adhesion and corrosion resistance to the substrate, and the addition of silver-plated mirror aluminum powder that is not easily oxidized can not only give the primer layer a better light reflectivity, but also ensure its high gloss for long-term use. Component B of the topcoat preferably contains carboxyl-terminated polyester resin as the main raw material, which interacts with other components to form better interface compatibility with the primer layer, and component B has high permeability as a whole, and under the synergistic effect of the modified glass microspheres, can give the powder coating a significant reflective property.

[0027] 2. The present invention selects modified glass microspheres of different particle sizes for compound use, which can play a more excellent bridging role. After being treated with stearyl trimethyl ammonium chloride and ethyl acetate, not only the dispersion stability of the modified glass microspheres can be improved, but also a certain electrostatic effect and steric hindrance effect can be given to the modified glass microspheres, which is beneficial to the subsequent treatment agent (vinyl trimethoxy silane and vinyl triethoxy silane), and vinyl is introduced on the surface of the modified glass microspheres, thereby increasing the bonding between the modified glass microspheres and the substrate, and the adhesion compatibility is more excellent, reducing the breakage rate in the preparation process and the peeling in the application process, and ensuring the reflective performance of the powder coating for long-term use.

[0028] 3. After the optimization of the formula and process, the present invention can obtain a powder coating with significant reflective effect as a whole, which is suitable for the fields of traffic safety, building decoration, consumer emergency and so on. DETAILED DESCRIPTION

[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with its embodiments. It should be understood that the specific implementation methods described herein are only used to explain the present invention and do not limit the scope of protection of the present invention.

[0030] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used herein in the specification of the present invention are only for the purpose of describing specific embodiments and are not intended to limit the present invention. The term "and / or" used herein includes any and all combinations of one or more related listed items.

[0031] In one embodiment of the present invention, a powder coating for reflective marking is provided, wherein the powder coating comprises a component A capable of forming a base coating and a component B capable of forming a top coating;

[0032] Wherein, the component A comprises the following raw materials in parts by weight:

[0033] 30 to 45 parts of epoxy resin, 30 to 45 parts of carboxyl-terminated polyester resin, 5 to 35 parts of transparent powder, 0.5 to 2 parts of leveling agent, 0.5 to 2 parts of brightener, 0.5 to 1 part of adhesion promoter, 0.2 to 0.5 parts of benzoin, 0.5 to 2 parts of defoamer, 0.5 to 2 parts of antioxidant, 0 to 1 part of pigment, 0.5 to 1 part of aligning agent, 0.5 to 1.5 parts of silver-plated mirror aluminum powder and 0.1 to 0.2 parts of desiccant;

[0034] Wherein, the component B comprises the following raw materials in parts by weight:

[0035] 80 to 95 parts of terminal carboxyl polyester resin, 6 to 7 parts of triglycidyl isocyanurate, 2 to 10 parts of modified glass microspheres, 0.5 to 2 parts of leveling agent, 0.2 to 0.5 parts of anti-scratch agent, 0.2 to 0.5 parts of benzoin, 0.5 to 1 parts of antioxidant, 0.2 to 0.5 parts of ultraviolet absorber and 0.1 to 0.2 parts of desiccant.

[0036] In one embodiment, in component A, the epoxy value of the epoxy resin is 0.098 eq / 100 g to 0.143 eq / 100 g, and the softening point is 89° C. to 99° C.

[0037] In one embodiment, in component A, the acid value of the carboxyl polyester resin is 60 mgKOH / g to 75 mgKOH / g, and the softening point is 95 to 120°C.

[0038] In one embodiment, in component A, the transparent powder is silicate powder.

[0039] In one embodiment, in component A, the leveling agent is a polyester-modified silicone leveling agent.

[0040] In one embodiment, in component A, the adhesion promoter is a multifunctional adhesion promoter.

[0041] In one embodiment, in component A, the defoaming agent is a polyether-modified silicone defoaming agent.

[0042] In one embodiment, in component A, the antioxidant is a hindered phenol antioxidant.

[0043] In one embodiment, in component A, the alignment agent is ethylene-vinyl acetate copolymer wax copolymer.

[0044] In one embodiment, in component A, the median particle size of the silver-plated mirror aluminum powder is 5 μm to 10 μm.

[0045] In one embodiment, in component A, the desiccant is aluminum oxide with a specific surface area of ​​(100±10) m 2 / g, and the average particle size is 10nm~13nm.

[0046] In one embodiment, in component B, the acid value of the carboxyl-terminated polyester resin is 32 mgKOH / g to 38 mgKOH / g, the viscosity @200°C (mPa.s) is 1500 to 2500, and the glass transition temperature is 64 to 67°C.

[0047] In one embodiment, the preparation method of the modified glass microspheres is:

[0048] Mixing vinyl trimethoxy silane and vinyl triethoxy silane in a mass ratio of (1 to 5): (1 to 3) to obtain a treating agent;

[0049] Glass microbeads of different particle sizes are added to a mixture containing stearyltrimethylammonium chloride, ethyl acetate and water, stirred at a speed of 100 r / min to 150 r / min for 20 min to 30 min, then sprayed with the treating agent in a rotary dryer at a speed of 10 r / min to 20 r / min and a temperature of 80°C to 90°C, and the rotary treatment is continued for 2h to 3h under the same rotary conditions to obtain modified glass microbeads.

[0050] Furthermore, the glass microspheres are mixed by the following particle size ratios in mass percentage: 10 μm to 30 μm particle size accounts for 15% to 20%, 31 μm to 50 μm particle size accounts for 25% to 30%, 51 μm to 80 μm particle size accounts for 30% to 35%, 81 μm to 120 μm particle size accounts for 7% to 10%, and 121 μm to 150 μm particle size accounts for 5% to 10%.

[0051] In one embodiment, the mass ratio of stearyl trimethyl ammonium chloride, ethyl acetate and water is (7-9): (1-3): (5-9).

[0052] In one of the embodiments, the material-liquid ratio of the glass microspheres to the mixed liquid is (1-3) g / 10 mL.

[0053] In one embodiment, the added amount of the treatment agent accounts for 10% to 20% of the mass of the glass microspheres.

[0054] In one embodiment, in component B, the leveling agent is an organic silicon modified acrylic polymer, and further is a polyester modified organic silicon leveling agent.

[0055] In one embodiment, in component B, the antioxidant is a hindered phenol antioxidant.

[0056] In one embodiment, in component B, the ultraviolet absorber is an o-hydroxydimethyl benzophenone compound.

[0057] In one embodiment, in component B, the desiccant is aluminum oxide with a specific surface area of ​​(100±10) m 2 / g, and the average particle size is 10nm~13nm.

[0058] In addition, the present invention also provides a method for preparing a powder coating, which is used to prepare the powder coating for the reflective marking, and the method comprises the following steps:

[0059] Add epoxy resin, carboxyl-terminated polyester resin, transparent powder, leveling agent, brightener, adhesion promoter, benzoin, defoamer, antioxidant, pigment and aligning agent into a mixing device and mix them evenly, and then perform a first melt extrusion and a first ACM grinding process to obtain a mixture;

[0060] Adding the silver-plated mirror aluminum powder, the desiccant and the mixture into a bonding device for bonding treatment, and then sieving to obtain component A capable of forming a primer layer;

[0061] Add the terminal carboxyl polyester resin, triglycidyl isocyanurate, modified glass microbeads, leveling agent, anti-scratch agent, benzoin, antioxidant, ultraviolet absorber and desiccant into a mixing device and mix evenly, and then undergo a second melt extrusion and a second ACM grinding process to obtain component B that can form a topcoat.

[0062] In one embodiment, the conditions of the first melt extrusion are: screw speed is 40HZ~45HZ, melting zone temperature is 90℃~105℃, and mixing zone temperature is 110℃~120℃.

[0063] In one embodiment, the conditions of the first ACM grinding process are: main grinding frequency 35HZ~45HZ, auxiliary grinding frequency 18HZ~30HZ, and feeding frequency 18HZ~25HZ.

[0064] In one embodiment, the screening process uses a 140-160 mesh screen.

[0065] In one embodiment, the bonding treatment conditions are: bonding temperature is 25℃~35℃, cold bonding speed is 900rpm~1000rpm, cooling speed is 400rpm~500rpm, cold water temperature is 17℃~19℃, and bonding stage time is 600s~900s.

[0066] In one embodiment, the conditions of the second melt extrusion are: a screw speed of 35HZ-40HZ, a melting zone temperature of 110°C-120°C, and a mixing zone temperature of 120°C-135°C.

[0067] In one embodiment, the conditions of the second ACM grinding process are: main grinding frequency 30HZ~35HZ, auxiliary grinding frequency 15HZ~25HZ, and feeding frequency 18HZ~25HZ.

[0068] In addition, the present invention further provides an application of the powder coating, wherein the application is the application of the powder coating in a road reflective sign, and the application method is:

[0069] The substrate is pretreated, and then component A is sprayed on it, placed in a curing furnace, and cured at a temperature of 150°C for 10 minutes to form a primer layer with a thickness of 60μm to 100μm; after being taken out of the furnace, component B is sprayed on it, and then placed in a curing furnace, and cured at a temperature of 210°C for 15 minutes to form a top coating layer with a thickness of 100μm to 150μm.

[0070] The embodiments of the present invention will be described in detail below with reference to specific examples.

[0071] Embodiment 1:

[0072] Select glass microspheres with the following particle size ratios for mixing: 17% of the particle size of 10 μm to 30 μm, 28% of the particle size of 31 μm to 50 μm, 35% of the particle size of 51 μm to 80 μm, 10% of the particle size of 81 μm to 120 μm, and 10% of the particle size of 121 μm to 150 μm; then add a mixed solution (stearyl trimethyl ammonium chloride, ethyl acetate and water in a mass ratio of 7:3:7) to the glass microspheres at a solid-liquid ratio of 3 g / 10 mL, stir at a speed of 100 r / min for 30 min, then spray a treatment agent (vinyl trimethoxy silane and vinyl triethoxy silane in a mass ratio of 3:2) accounting for 15% of the mass of the glass microspheres in a rotary dryer at a speed of 20 r / min and a temperature of 85° C., and continue to rotate for 2 h under the same rotation conditions to obtain modified glass microspheres for standby use;

[0073] By weight, 35 parts of epoxy resin, 38 parts of carboxyl-terminated polyester resin, 22 parts of silicate powder, 1 polyester-modified silicone leveling agent, 1 part of brightener, 1 part of adhesion promoter, 0.3 parts of benzoin, 1 part of polyether-modified silicone defoamer, 1 part of hindered phenol antioxidant, 0.5 parts of pigment and 1 part of ethylene-vinyl acetate copolymer wax copolymer are added to a mixing device and mixed evenly, and then subjected to a first melt extrusion and the conditions of the first melt extrusion are: a screw speed of 40 Hz, a melting zone temperature of 105° C., and a mixing zone temperature of 120° C., and then subjected to a first ACM grinding treatment and the conditions of the first ACM grinding treatment are: a main grinding frequency of 35 Hz, a secondary grinding frequency of 18 Hz, and a feeding frequency of 20 Hz, to obtain a mixture;

[0074] 1.5 parts of silver-plated mirror aluminum powder, 0.2 parts of aluminum oxide and the mixture are added into a bonding device for bonding treatment, and the bonding treatment conditions are as follows: bonding temperature is 30° C., cold bonding speed is 900 rpm, cooling speed is 400 rpm, cold water temperature is 17° C., bonding stage time is 700 s, and then sieving is performed using a 140-mesh sieve to obtain component A capable of forming a primer layer;

[0075] By weight, 93 parts of terminal carboxyl polyester resin, 7 parts of triglycidyl isocyanurate, 7 parts of modified glass microbeads, 1 part of polyester modified silicone leveling agent, 0.3 parts of anti-scratch agent, 0.3 parts of benzoin, 0.7 parts of hindered phenol antioxidant, 0.5 parts of o-hydroxydimethyl benzophenone compound and 0.1 parts of aluminum oxide are added to a mixing device and mixed evenly, and then subjected to a second melt extrusion and the conditions of the second melt extrusion are: a screw speed of 40HZ, a melting zone temperature of 120°C, a mixing zone temperature of 120°C, and then a second ACM grinding treatment is performed and the conditions of the second ACM grinding treatment are: a main grinding frequency of 30HZ, a secondary grinding frequency of 15HZ, and a feeding frequency of 18HZ to obtain component B capable of forming a top coating.

[0076] The substrate was pretreated, then component A was sprayed on it, placed in a curing oven, and cured at 150°C for 10 minutes to form a primer layer with a thickness of 80 μm. Related performance tests were performed, and the results are shown in Table 1.

[0077] After being taken out of the oven, component B was sprayed on the surface, and then placed in a curing oven and cured at 210°C for 15 minutes to form a top coating with a thickness of 100 μm. Related performance tests were carried out, and the results are shown in Table 2.

[0078] Embodiment 2:

[0079] The difference between Example 2 and Example 1 is that the raw material ratio of component A in Example 2 is different, and the other parts are the same as Example 1. Component A in Example 2 includes the following raw materials in parts by weight:

[0080] 38 parts of epoxy resin, 40 parts of terminal carboxyl polyester resin, 20 parts of silicate powder, 0.5 parts of polyester modified silicone leveling agent, 1 part of brightener, 0.8 parts of adhesion promoter, 0.4 parts of benzoin, 1 part of polyether modified silicone defoamer, 2 parts of hindered phenol antioxidant, 0.5 parts of pigment, 0.8 parts of ethylene-vinyl acetate copolymer wax copolymer, 1.2 parts of silver-plated mirror aluminum powder and 0.2 parts of aluminum oxide.

[0081] Embodiment 3:

[0082] The difference between Example 3 and Example 1 is that the raw material ratio of component B in Example 3 is different, and the other parts are the same as Example 1. Component B in Example 3 includes the following raw materials in parts by weight:

[0083] 85 parts of terminal carboxyl polyester resin, 7 parts of triglycidyl isocyanurate, 8 parts of modified glass microspheres, 2 parts of polyester modified silicone leveling agent, 0.4 parts of anti-scratch agent, 0.3 parts of benzoin, 0.8 parts of hindered phenol antioxidant, 0.4 parts of o-hydroxydimethyl benzophenone compound and 0.2 parts of aluminum oxide.

[0084] Embodiment 4:

[0085] The difference between Example 4 and Example 1 is that the preparation method of the modified glass microspheres used in Example 4 is different, and the other parts are the same as Example 1. The preparation method of the modified glass microspheres in Example 4 is as follows:

[0086] Glass microspheres with the following particle size ratios are selected for mixing: 18% of the particle size of 10 μm to 30 μm, 30% of the particle size of 31 μm to 50 μm, 35% of the particle size of 51 μm to 80 μm, 8% of the particle size of 81 μm to 120 μm, and 9% of the particle size of 121 μm to 150 μm; then, a mixed solution (stearyl trimethyl ammonium chloride, ethyl acetate and water in a mass ratio of 8:2:7) is added to the glass microspheres at a solid-liquid ratio of 3 g / 10 mL, and the mixture is stirred at a speed of 100 r / min for 30 min, and then a treatment agent (vinyl trimethoxy silane and vinyl triethoxy silane in a mass ratio of 4:1) accounting for 18% of the mass of the glass microspheres is sprayed in a rotary dryer at a speed of 20 r / min and a temperature of 80°C, and the rotary treatment is continued for 2 h under the same rotation conditions to obtain modified glass microspheres for standby use.

[0087] Comparative Example 1:

[0088] The difference between Comparative Example 1 and Example 1 is that no silver-plated mirror aluminum powder is added to Component A of Comparative Example 1, and the rest is the same as Example 1.

[0089] Comparative Example 2:

[0090] The difference between Comparative Example 2 and Example 1 is that the raw material ratio of component A in Comparative Example 2 is different, and the others are the same as Example 1. Component A in Comparative Example 2 includes the following raw materials in parts by weight:

[0091] 78 parts of epoxy resin, 20 parts of silicate powder, 0.5 parts of polyester modified silicone leveling agent, 1 part of brightener, 0.8 parts of adhesion promoter, 0.4 parts of benzoin, 1 part of polyether modified silicone defoamer, 2 parts of hindered phenol antioxidant, 0.5 parts of pigment, 0.8 parts of ethylene-vinyl acetate copolymer wax copolymer, 1.2 parts of silver-plated mirror aluminum powder and 0.2 parts of aluminum oxide.

[0092] Comparative Example 3:

[0093] The difference between Comparative Example 3 and Example 1 is that the raw material ratio of component B in Comparative Example 3 is different, and the other parts are the same as Example 1. Component B in Comparative Example 3 includes the following raw materials in parts by weight:

[0094] 80 parts of polyamide resin, 7 parts of triglycidyl isocyanurate, 7 parts of modified glass microspheres, 1 part of polyester modified silicone leveling agent, 0.3 parts of anti-scratch agent, 0.3 parts of benzoin, 0.7 parts of hindered phenol antioxidant, 0.5 parts of o-hydroxydimethylbenzophenone compound and 0.1 parts of aluminum oxide.

[0095] Comparative Example 4:

[0096] The difference between Comparative Example 4 and Example 1 is that the glass microspheres in Comparative Example 4 are not modified and are directly added for use, and the rest is the same as Example 1.

[0097] Comparative Example 5:

[0098] The difference between Comparative Example 5 and Example 1 is that in Comparative Example 5, only glass microbeads with a particle size of 100 μm are used, and the rest are the same as in Example 1.

[0099] Comparative Example 6:

[0100] The difference between Comparative Example 6 and Example 1 is that only glass microbeads with a particle size of 10 μm are used in Comparative Example 6, and the rest are the same as Example 1.

[0101] Comparative Example 7:

[0102] The difference between Comparative Example 7 and Example 1 is that the preparation method of the modified glass microspheres in Comparative Example 7 is different, and the other methods are the same as Example 1. Specifically, the preparation method of the modified glass microspheres in Comparative Example 7 is as follows:

[0103] Glass microspheres with the following particle size ratios are selected for mixing: 17% of the particle size of 10 μm to 30 μm, 28% of the particle size of 31 μm to 50 μm, 35% of the particle size of 51 μm to 80 μm, 10% of the particle size of 81 μm to 120 μm, and 10% of the particle size of 121 μm to 150 μm; then, a mixed solution (stearyl trimethyl ammonium chloride, ethyl acetate and water in a mass ratio of 7:3:7) is added to the glass microspheres at a solid-liquid ratio of 3 g / 10 mL, and the mixture is stirred at a speed of 100 r / min for 30 min, and then rotated in a rotary dryer at a speed of 20 r / min and a temperature of 85°C for 1 h to obtain modified glass microspheres for standby use.

[0104] Comparative Example 8:

[0105] The difference between Comparative Example 8 and Example 1 is that the preparation method of the modified glass microspheres in Comparative Example 8 is different, and the other steps are the same as those in Example 1. Specifically, the preparation method of the modified glass microspheres in Comparative Example 8 is as follows:

[0106] Glass microspheres with the following particle size ratios are selected for mixing: 17% of 10 μm to 30 μm, 28% of 31 μm to 50 μm, 35% of 51 μm to 80 μm, 10% of 81 μm to 120 μm, and 10% of 121 μm to 150 μm; then, a treating agent accounting for 15% of the mass of the glass microspheres (vinyl trimethoxy silane and vinyl triethoxy silane in a mass ratio of 3:2) is added to the glass microspheres at a solid-liquid ratio of 3 g / 10 mL, and the mixture is stirred at a speed of 100 r / min for 1 h to obtain modified glass microspheres for standby use.

[0107] Comparative Example 9:

[0108] The difference between Comparative Example 9 and Example 1 is that no modified glass microspheres are added in Comparative Example 9, and the rest is the same as Example 1.

[0109] The primer layers of Examples 1 to 4 and Comparative Examples 1 to 2 were subjected to relevant performance tests, referring to HG / T-2006. The primer layers in Comparative Examples 3 to 9 were the same as those in Example 1 and are not described in detail here. The results are shown in Table 1.

[0110] Table 1: Performance test results of base coating

[0111]

[0112] From the data analysis of Table 1, it can be seen that the base coating of the present invention is excellent in combination with the substrate, has excellent adhesion, and has good gloss. Specifically, the difference between Comparative Example 1 and Example 1 is that no silver-plated mirror aluminum powder is added in Comparative Example 1, but the gloss of the base coating is significantly worse than that of the base coating in Example 1, and the mechanical properties are also reduced, indicating that the addition of silver-plated mirror aluminum powder can significantly improve the mechanical properties and gloss of the base coating. The difference between Comparative Example 2 and Example 1 is that no carboxyl-terminated polyester is added, but the mechanical properties and adhesion of the base coating are worse than those in Example 1, indicating that the present invention can help improve the adhesion and mechanical properties of the base coating to the substrate and ensure its application performance by optimizing the raw materials for preparing the base coating.

[0113] The products after the top coatings in Examples 1 to 4 and Comparative Examples 1 to 9 were subjected to an aging resistance test (xenon lamp), and the results are shown in Table 2 below.

[0114] Table 2: Aging resistance test results

[0115]

[0116]

[0117] From the data analysis of Table 2, it can be seen that in this application, by optimizing component A of the base coating and component B of the top coating, a coating with excellent light retention rate and aging resistance and good uniformity can be obtained as a whole, which can be better used in the preparation of luminous identification products. Specifically, compared with Example 1, the light retention rates in Comparative Examples 1 to 2 are not as good as those in Example 1, and the color difference is obvious, indicating that the raw materials used to prepare the base coating will also affect the performance of the overall product. Different polyamide resins are selected in component B of Comparative Example 3, which will affect the aging resistance of the coating, and the transparency of the polyamide resin is not as good as the preferred terminal carboxyl polyester resin in this application, which will also affect the light retention rate of the coating. The glass microbeads in Comparative Example 4 have not been modified, so that the powder coating has the problem of being difficult to disperse during the preparation and application process, which will affect its application effect, and no vinyl groups and other groups are introduced on the surface, and the compatibility with the matrix components is poor, which will affect the overall light retention rate of the coating. The difference between Comparative Examples 5 to 6 and Example 1 is that the particle size of the glass microbeads is different. It can be seen that the grading ratio of the glass microbeads will also affect the final light retention rate of the coating. The present invention optimizes the particle size of the glass microbeads to help improve the reflective effect. The modification methods of the glass microbeads in Comparative Examples 7 and 8 are different, but the coating effects formed are worse than those in Example 1, indicating that the glass microbeads of the present application have better compatibility with the substrate after modification, and excellent interface effects, so that the glass microbeads can exert their better reflective effect. In Comparative Example 9, no modified glass microbeads were added, and the light retention rate was significantly worse than that of Example 1, which affects its application.

[0118] The reflective performance of the products after the top coating layers in Examples 1 to 4 and Comparative Examples 1 to 9 were tested, and the results are shown in Table 3 below.

[0119] Table 3: Reflective performance test results

[0120]

[0121]

[0122] From the data analysis of Table 3, it can be seen that the present invention can obtain a product with excellent reflective effect by optimizing the raw materials for preparing the base coat and the top coat, and is suitable for the preparation of reflective identification products. Specifically, in the comparative example 1 of the present application, no silver-plated mirror aluminum powder is added, and the mirror effect of the base coat is poor or even no mirror effect, resulting in poor overall reflective effect, indicating that the addition of silver-plated mirror aluminum powder in the base coat can synergize with the modified glass microbeads in the top coat to achieve a better reflective purpose. In the comparative example 2, no carboxyl-terminated polyester resin is added to component A, which not only affects the bonding force between the base coat and the substrate, but also affects the interface between the raw materials of the top coat and the raw materials of the base coat, thereby having a certain effect on the reflective performance. In comparative example 3, polyamide resin is used to replace the carboxyl-terminated polyester resin. The polyamide resin with lower transparency than the carboxyl-terminated polyester resin will affect the reflective performance of the modified glass microbeads, and as the main raw material of the top coat, its compatibility with other ingredients is not as good as the carboxyl-terminated polyester resin of the present invention, so that the reflective performance of the final product is poor, indicating that the preferred raw materials for preparing component B of the present invention also help to provide reflective performance. The glass beads in Comparative Example 4 have not been modified, and obvious agglomeration occurs during direct addition and use. After forming the topcoat, the adhesion to the substrate is poor, and the glass beads are easy to peel off, resulting in poor reflective effect. Comparative Examples 5 and 6 both use glass beads of a single particle size, and their reflective performance is worse than that of Example 1, indicating that the present invention adds glass beads of different particle sizes for mixed use. On the one hand, glass beads of different particle sizes are mixed for use, and the probability of glass beads with smaller particle sizes being impacted by the environment in the topcoat is small, and they are protected to a certain extent, and the integrity is better; on the other hand, if only glass beads of a single particle size are added, the probability of agglomeration is high if the particle size is too small, and the overall specific surface is small if the particle size is too large, which will affect the reflective effect. Therefore, the present invention helps to improve the reflective performance by preferably using glass beads of different particle sizes. The preparation methods of the modified glass microspheres in Comparative Examples 7 and 8 are different, but the reflective performance is worse than that of Example 1, which shows that the present invention can promote the interaction between the modified glass microspheres and the substrate by optimizing the preparation method of the modified glass microspheres, increase the interfacial bonding force between the modified glass microspheres and the substrate, and at the same time, have high dispersion stability and exert better reflective performance. In Comparative Example 9, no modified glass microspheres are added. Since the top coating is made of highly transparent materials as a whole, and silver-plated mirror aluminum powder is added to the bottom coating, there is a certain reflective effect under the interaction of the raw materials, but the reflective effect is poor and cannot meet the use requirements.

[0123] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0124] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A powder coating for reflective marking, characterized in that: The powder coating comprises component A capable of forming a base coating and component B capable of forming a top coating; Wherein, the component A comprises the following raw materials in parts by weight: 30 to 45 parts of epoxy resin, 30 to 45 parts of carboxyl-terminated polyester resin, 5 to 35 parts of transparent powder, 0.5 to 2 parts of leveling agent, 0.5 to 2 parts of brightener, 0.5 to 1 part of adhesion promoter, 0.2 to 0.5 parts of benzoin, 0.5 to 2 parts of defoamer, 0.5 to 2 parts of antioxidant, 0 to 1 part of pigment, 0.5 to 1 part of aligning agent, 0.5 to 1.5 parts of silver-plated mirror aluminum powder and 0.1 to 0.2 parts of desiccant; Wherein, the component B comprises the following raw materials in parts by weight: 80 to 95 parts of terminal carboxyl polyester resin, 6 to 7 parts of triglycidyl isocyanurate, 2 to 10 parts of modified glass microspheres, 0.5 to 2 parts of leveling agent, 0.2 to 0.5 parts of anti-scratch agent, 0.2 to 0.5 parts of benzoin, 0.5 to 1 parts of antioxidant, 0.2 to 0.5 parts of ultraviolet absorber and 0.1 to 0.2 parts of desiccant.

2. The powder coating according to claim 1, characterized in that In component A, the epoxy value of the epoxy resin is 0.098 eq / 100 g to 0.143 eq / 100 g, and the softening point is 89° C. to 99° C.

3. The powder coating according to claim 1, characterized in that In component A, the acid value of the carboxyl polyester resin is 60 mgKOH / g to 75 mgKOH / g, and the softening point is 95 to 120°C.

4. The powder coating according to claim 1, characterized in that In component B, the acid value of the carboxyl-terminated polyester resin is 32 mgKOH / g to 38 mgKOH / g, the viscosity @200°C (mPa.s) is 1500 to 2500, and the glass transition temperature is 64°C to 67°C.

5. The powder coating according to claim 1, characterized in that: The preparation method of the modified glass microspheres is as follows: Mixing vinyl trimethoxy silane and vinyl triethoxy silane in a mass ratio of (1 to 5): (1 to 3) to obtain a treating agent; Glass microbeads of different particle sizes are added to a mixture containing stearyltrimethylammonium chloride, ethyl acetate and water, stirred at a speed of 100 r / min to 150 r / min for 20 min to 30 min, then sprayed with the treating agent in a rotary dryer at a speed of 10 r / min to 20 r / min and a temperature of 80°C to 90°C, and the rotary treatment is continued for 2h to 3h under the same rotary conditions to obtain modified glass microbeads.

6. The powder coating according to claim 5, characterized in that In component B, the glass microspheres are mixed by the following particle size ratios by mass percentage: 10 μm to 30 μm particle size accounts for 15% to 20%, 31 μm to 50 μm particle size accounts for 25% to 30%, 51 μm to 80 μm particle size accounts for 30% to 35%, 81 μm to 120 μm particle size accounts for 7% to 10%, and 121 μm to 150 μm particle size accounts for 5% to 10%.

7. A method for preparing a powder coating, characterized in that: The preparation method is used to prepare the powder coating for reflective marking according to any one of claims 1 to 6, and the preparation method comprises the following steps: Add epoxy resin, carboxyl-terminated polyester resin, transparent powder, leveling agent, brightener, adhesion promoter, benzoin, defoamer, antioxidant, pigment and aligning agent into a mixing device and mix them evenly, and then perform a first melt extrusion and a first ACM grinding process to obtain a mixture; Adding the silver-plated mirror aluminum powder, the desiccant and the mixture into a bonding device for bonding treatment, and then sieving to obtain component A capable of forming a primer layer; Add the terminal carboxyl polyester resin, triglycidyl isocyanurate, modified glass microbeads, leveling agent, anti-scratch agent, benzoin, antioxidant, ultraviolet absorber and desiccant into a mixing device and mix evenly, and then undergo a second melt extrusion and a second ACM grinding process to obtain component B that can form a topcoat.

8. The preparation method according to claim 7, characterized in that: The conditions of the first melt extrusion are: screw speed of 40HZ-45HZ, melting zone temperature of 90°C-105°C, mixing zone temperature of 110°C-120°C.

9. The preparation method according to claim 7, characterized in that: The bonding treatment conditions are as follows: bonding temperature is 25°C to 35°C, cold bonding speed is 900rpm to 1000rpm, cooling speed is 400rpm to 500rpm, cold water temperature is 17°C to 19°C, and bonding stage time is 600s to 900s.

10. An application of a powder coating, characterized in that: The application is the application of the powder coating prepared in claim 7 in the preparation of reflective marking products, and the application method is: The substrate was pretreated, then component A was sprayed on the substrate, and the substrate was placed in a curing oven and cured at 150° C. for 10 min to form a primer layer with a thickness of 60 μm to 100 μm. After being taken out of the oven, component B is sprayed on the surface, and then the surface is placed in a curing oven and cured at a temperature of 210° C. for 15 minutes to form a surface coating with a thickness of 100 μm to 150 μm.

Citation Information

Patent Citations

  • High-antistatic powder coating and preparation method thereof

    CN114907736A

  • Stain-resistant coating capable of reflecting pearlescent flicker and preparation method of stain-resistant coating

    CN115948094A